Synchronous adenocarcinoma of small bowel, appendix and rectum - Wan Mokhtar, Wan Aini Faizah; Yunus, Mohammad Alif; Rahim, M. Fadliyazid A.; Ahmadi, Farah Hanum; Omar, Siti Zarqah (International Surgery Journal, 2023)
Synchronous colorectal carcinoma (SCRC) has been relatively a rare case as nature of the disease is not well established, due to limited data regarding the disease. The incident of SCRC showed by ranges from 2.3 to 12.4%, most cases were 2 site pathologies, involving colon and rectum. Due to its rarity, the diagnostic and treatment modalities provide such challenges to clinician. We reported a rare case in which patient had 3 sites synchronous adenocarcinoma of small bowel, appendix and rectum. Diagnosis was made intra-operatively as patient presented with acute small bowel obstruction. Here we discussed regarding the challenges in detecting and managing the synchronous lesion, including the interesting pathobiology of the disease.